Prognostic Value of Pretreatment Serum Transthyretin Level in Patients with Gastrointestinal Cancers. (3rd June 2019) - Luo, Hongliang; Huang, Jun; Zhu, Zhengming; Zhu, Peiqian
Abstract : Background . Many studies have shown the link between the pretreatment serum transthyretin and prognosis in gastrointestinal (GI) cancers. However, based on the conclusion, the initial findings were inconsistent. Hence, this meta-analysis was performed to identify the prognostic values of the pretreatment serum transthyretin in GI cancers. Methods . Previous studies published before November 2018 were collected from a comprehensive literature search of several databases. The pooled hazard ratios (HRs) and 95% confidence intervals (CIs) were applied in the assessment of the intensity of associations. Also, the publication bias and the robustness of merged data were assessed. All statistical analyses were undertaken using STATA/SE 14.1. Results . The combined data indicated that the pretreatment serum transthyretin level was related to the prognosis in GI cancers. The group with reduced pretreatment transthyretin had a significantly worse overall survival (OS) (HR = 1.71, 95% CI: 1.37-2.05). The subgroup analysis for OS further showed the predictive value of transthyretin. In addition, the low serum transthyretin level could be an unfavorable factor for recurrence-free survival (RFS) or progression-free survival (PFS) (HR = 1.66, 95% CI: 1.14-2.18) in GI cancers. Conclusion . The low pretreatment serum transthyretin level implies an unfavorable prognosis for patients with GI cancers. The monitoring of pretreatment transthyretin level could contribute to the risk stratification and individualized therapy in GI cancers.